ETHNOSCIENCE STUDIES OF THE ANGKOLA BATAK CULINARY IN SOUTH TAPANULI REGENCY AS AN EFFORT TO PRESERVE LOCAL CULTURAL VALUES - Wina Dyah Puspita Sari; Cicik Suriani; Aswarina Nasution; Ermy Veronica Sitompul (ISER (Indonesian Science Education Research), 2023)
This research aims to find out the types of typical food of the Batak Angkola tribe, the ingredients and processing methods for typical food of the Batak Angkola tribe, as well as explaining the original science of the typical food of the Batak Angkola tribe in an effort to develop science learning tools. This research was carried out in the South Tapanuli Regency, North Sumatra Province. This research was carried out in June-July 2023. The type of research used in this research was descriptive qualitative research. The data sources used in this research are primary data and secondary data using interview methods, direct observation of the Angkola Batak community. The results obtained in this research were various types of typical food from the Angkola Batak tribe, namely: Holat, various types of snacks including Panggelong, Lading-lading, golang-golang, Wajik and various types of processed salak fruit. The ingredients for the typical Batak Angkola regional food are obtained from the area itself. The main ingredient for making hotal is using shaved balaka plants, for making panggelong, lading-lading, golang-golang and wajik using rice flour which is produced directly in the area. Every typical Angkola Batak food production has its own science concept which is specialized in the production of each food